Contribuição do turismo rural na sustentabilidade das propriedades lindeiras ao lago de Itaipu no Paraná - Strassburger, Nândri Cândida (2023)
The argument that tourism is a promising alternative for employment and income to agricultural families has been dispersed progressively more, once this activity dynamizes economically the rural means by aggregating monetary value to the property’s productive means. Beyond that, it is seen as potentially sustainable, because, beyond the economical advantages, its practice can contribute to the preservation and revitalization of the environment and to the recuperation and valorization of the rural families and communities’ social-cultural traditions. The objective was to investigate the contribution that touristic activity promotes in rural properties neighboring Itaipu Lake in the state of Paraná. To reach the objective of the study, two articles were developed, the first article presents a data collection of bibliometric nature to understand this activity in the Brazilian rural means. The bibliographical study using public databases, which analyzed the scientific production relating to the dissertations and theses portfolio which are encountered in the Brazilian Digital Library of Theses and Dissertations which approach the theme rural tourism in the context of family agriculture, across the years of 2010 through 2019. The results show that studies related to rural tourism have similarities. More effectively, what sustainability actions point to the activity as a potential alternative for sustainable rural development. The second article investigated the contribution of rural tourism to the sustainability of rural properties bordering Lake Itaipu in Paraná, as the countryside is no longer just a place of agricultural production for its sustainability. It is also the scene of sociocultural and environmental interactions with the people of the city, through tourist activities, wich promote the appreciations of its productivity as the value and care for the environment. In this sense, the study was of descriptive nature with a transversal cut in 2022 disregarding the evolution of data in relation to time, the primary source data was collected at first through interviews and the secondary source data was collected through scientific literature, official websites and legislation pertinent to the theme, being treated by simple statistics and analyzed descriptively. The results showed that the economic factor was considered the most important to guarantee the sustainability of the tourist activity and the property as a whole. The second was the environmental and social factors. The contribution of this study involves showing that in touristic activity the care with the environment is fundamental and necessary, that this activity can add value to production, through the sale of products during visits and increase awareness of care for the environment, appreciation of culture and gastronomy, in addition to increase the income and sustainability of the farmer who stays on the land. In a systemic way, these aspects which contribute to the promotion of sustainability of the rural tourism.